Pendampingan Pemanfaatan Larutan KNO3 terhadap Perkecambahan dan Pertumbuhan Awal Benih Padi di Desa Sumbersalak Kecamatan Ledokombo Kabupaten Jember - Adin Novitasari; Sri Rejeki Utami; Aminatun Nisa; Ummi Sholikah; Ahmad Ilham Tanzil; Wahyu Indra Duwi Fanata; Tri Ratnasari; Yusuf Rachmandika (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Farmers in Sumbersalak Village, Ledokombo, Jember Regency still depend on rice as the main commodity in their business. One important component that supports the success of rice cultivation is the availability of quality seeds. One obstacle faced in rice seed production is dormancy. One effort to improve the quality of seeds that have been stored for a long time is to give rice seeds special treatment in the hope of improving germination and early growth. The method used is participatory assistance, including dissemination of information, discussion, and direct practice of seed soaking. The activity was carried out in July 2025 at the Kenconowungu Farmer Group, involving 10 participants. The rice seeds were soaked in a 3% KNO3 solution for 24 hours. The results showed that the KNO3 treatment was effective as an invigoration technique that improved the physiological characteristics of the seeds, which had deteriorated during storage. The application of this technology was proven to increase the germination rate of local rice seeds to be faster and more uniform compared to those without treatment. Additionally, this assistance successfully improved farmers' understanding and independence in managing seeds in a practical and applicable manner.